Health Sector Evolution in Iran; A Short Review - Morteza Arab-zozani; Saeed Husseini barghazan (Shahid Sadoughi University of Medical Sciences, 2017)
Despite noticeable progresses and visible changes in health system of Iran, there are many shortages and gaps which make this system far away from ideal. In order to solve these problems and to visit goals set by the government a plan was launched to reform the health system in May 2014. These reforms encompassed seven sub-plans: decreasing in-patients' out-of -pocket (OOP) payments, supporting physicians to stay in deprived areas to improve healthcare services quality, planning presence of physicians in public hospitals to improve quality of their services, improving public hospital’s clinic visits quality, upgrading hoteling care quality in public hospitals, financial protecting of non-treatable diseases and special needs, as well as promoting natural childbirth. This manuscript reflects opinions of an expert dealing with this reform. On the one hand, there have been noticeable changes and achievements in this realm, such as 8.5 to 37 % reduction in in-patient OOP payment, coverage of 10.2 million people under national health insurance, and many other significant short-term achievements. On the other hand, instability of financial resources, irregularity of plans, weakness of the private health sector, and costs of reforms' implementation are main disadvantage of reforms. Reforms' designers are now working on payment systems of the providers to solve problems that arose as consequences of reforms and formulate structures to ensure about stability of financial resources even in future governments.